Enhancing Quality Assurance In Haematology Laboratory Sample Collection: Strategies For Identifying Sources Of Rejection And Mitigation – A Mini Review - Nur Ain Izzati Abdul Halim; Razan Hayati Zulkeflee; Rosnah Bahar; Hani Ajrina Zulkeflee; Nur Ilyia Syazwani Saidin; Ahmad Zakwan Mustafa; Nur Alia Najiehah Suhaimi; Wan Nor Fazila Hafizan Wan Nik (Penerbit Universiti Sultan Zainal Abidin, 2024)
Indexed by MyCite